Death's mistress [compact disc, unabridged] : sister of darkness - Goodkind, Terry (Goodkind, Terry. Nicci chronicles., 2016)
One-time lieutenant of the evil Emperor Jagang, the deadly Nicci, captured Richard Rahl in order to convince him that the Imperial Order stood for the greater good. But it was Richard who converted Nicci instead, and for years thereafter she served Richard and Kahlan as one of their closest friends, and one of their most lethal defenders. Now, with the reign of Richard and Kahlan finally stabilized, Nicci has set out on her own for new adventures. Her first job being to keep the unworldly prophet Nathan out of trouble.